An overview of removing heavy metals from sewage sludge: Achievements and perspectives. (November 2020) - Geng, Hui; Xu, Ying; Zheng, Linke; Gong, Hui; Dai, Lingling; Dai, Xiaohu
Abstract: The removal of heavy metals from sewage sludge (SS) is attracting increasing attention because the presence of toxic heavy metals in SS restricts its reuse or disposal, especially on land. This review presents an overview of research on the origin and chemical speciation of heavy metals in SS and describes methods for their removal. SS primarily absorbs heavy metals from wastewater via passive sorption and active uptake of biomass, resulting in the different chemical speciation. The advantages and disadvantages of the current methods for the removal of heavy metals from SS are analysed. The current methods focus on the removal efficiencies of heavy metals, which are high enough to meet the standard of land application, but the treatment cost, the change and retention of nutrients, and the effects on SS properties resulting from heavy metal removal are usually ignored. In this review, the main knowledge gaps are identified and proposals for future research are made. These should comprise determining the underlying mechanisms of current removal methods, optimising and integrating the removal methods, and establishing systematic evaluation standards for these methods. This review will help researchers develop new environmentally and economically friendly methods for the removal of heavy metals from SS. Graphical abstract: Image 1 Highlights: The origin and chemical speciation of heavy metals in sludge are analysed. Achievements of current methods for heavy metals removal are overviewed. Main knowledge gaps of current methods for heavy metals removal are identified. Future research on removing heavy metals from sewage sludge is proposed. Abstract : The main knowledge gaps of the current methods for removing heavy metals from SS are identified and proposals for future research are made.